Estimating the influence of social capital on entrepreneurial activity in the Russian regions - A. R. Klimanova (Russian Journal of Economics and Law, 2019)
Objective: to assess the impact of social capital on economic growth, welfare and entrepreneurial activity of the Russian regions.Methods: abstract-logical method, descriptive method, econometric modeling.Results: when preparing the literature review on the subject of the study, a consensus view was revealed that social capital is a multifactorial phenomenon with many elements, forms of manifestation and channels of influence on the development of socio-economic systems. The direction of the social capital impact significantly depends on its context.The paper shows that at different times different elements of social capital influence differently on the indicators of entrepreneurial activity in the Russian regions. In particular, two of the three main elements of social capital - trust capital and social media capital, - calculated according to the “GeoRating 2007” poll by “Public Opinion” foundation and the “Social Capital: alternative source of energy” report (2015), account for 14 to 18% of the differences between the Russian regions in the share of revenues of small enterprises in their gross regional product (GRP).It is significant that in the above two periods of observation the nature of this effect changed qualitatively. In particular, in2015 the capital of trust became more significant and began to have a negative impact on the GRP. The capital of social networks retained its positive influence on the dependent variable, but its importance in the model was somewhat reduced. Scientific novelty: the study proved the moderate influence of one of the elements of social capital - the capital of social networks - on the gross regional product of the Russian regions: its elasticity for this indicator is estimated at 0.1. The positive impact of capital norms and values on the level of welfare in the regions of Russia is also confirmed. It is concluded that the impact of open social capital has a positive influence on business activity, expressed in the number of small businesses per 10,000 people in the region of the Russian Federation. It is also shown that the capital of values and norms affected the dynamics of entrepreneurial activity in the period 2010-2015: it had a positive effect on the growth of the average number of employees of small enterprises and revenues from the sale of goods (works, services) of small enterprises in the regions of the Russian Federation. Practical significance: the results of the study can be used in the practical activities of the authorities forming the regional policy of entrepreneurship development in Russia.